Pre-conception and pre-natal diagnostic techniques act-draconian or a considerate de jure tamer - Khanna, Vasudha; Gopal, K. Madan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Principles of gender equity are an integral part of constitution. The constitution confers equal rights and opportunities on women; bars discrimination on the basis of sex and denounces practices derogatory to the dignity of women. In spite of this, discrimination against women and girls is almost universal. Forced abortions of female foetuses and prenatal sex determination results in millions of girls not being allowed to be born just because they are girls. Pre-conception and pre-natal diagnostic techniques (PC and PNDT) act were enacted in 1994, amended and effectively implemented in 2003 and strictly amended in 2011, to curb this heinous crime of female foeticide that was taking place due to prenatal diagnostic techniques for determination of the sex of the foetus and thus, to balance the disturbed sex ratio of the country. To achieve the said purposes, the act imposes penalties for the offences committed under this Act, including clerical errors. However, according to the radiologists, the PC and PNDT act has become draconian for all practicing sonologists and radiologists instead of serving the purpose of saving the girl child. This article, explaining the provisions of PC and PNDT act, addresses the concerns of sonologists and radiologists in the light of the judgements passed by Hon’ble Supreme Court of India. It further discusses the hindrances occurring in the usage of evolved medical technology due to the provisions of the Act thereby paving way towards a much-needed legitimate decision to settle the ongoing country-wide debate.